The relativity of sociodemographic determinism on the digital divide in high school students in Ecuador - Tirado Morueta, Ramón; Mendoza Zambrano, Damian; Marín Gutiérrez, Isidro; Mendoza Zambrano, Mariuxi (University of Southern California (USC), 2017)
Although the digital divide on physical access to the Internet in developing countries is closing with respect to developed countries, a new gap on the social usage of the Internet is opening. This study focuses on Ecuador for the purpose of (a) determining the level of access to Internet use of the younger sector of the population (high school students) and (b) understanding to what extent sociodemographic factors determine Internet access and its use. This study uses a random sample (3,754 individuals), stratified by provinces, which is representative of high school students in Ecuador. The results show that the influence of sociodemographic factors are higher with regard to the physical access to the Internet, and this influence decreases with regard to more complex levels of Internet usage (i.e., the data show that a high sociofamilial status does not guarantee access to more complex Internet usage levels; however, a low status is a risk factor).
Keywords: Recursos en Internet - Aspectos sociales; media literacy; digital literacy; digital divide